Is the Post-secondary Classroom a Chilly One for Women?: A Review of the Literature - Williams, Dana (Canadian Journal of Higher Education, 1990)
A review of the literature on gender bias in the post-secondary classroom reveals that in many cases women students do not participate in class discussions as much as men students. Cause and effect cannot be determined from these studies, but a female teacher and teacher training in sex equitable behaviour are two factors associated with increased female participation. Studies examining student evaluations of teachers reveal that female students rate their female professors higher than their male professors. Research examining post-secondary experiences leading to women's achievement and self-confidence after graduation suggests that attending a woman's college and having female teachers are important. Future research is needed to determine the cause and effect relationship between specific classroom variables on women's classroom participation, satisfaction, and achievement after graduation.